Environment as Cultural Heritage : The Armenian Diaspora’s Willingness to Pay to Protect Armenia’s Lake Sevan - Laplante, Benoit; Meisner, Craig; Wang, Hua (World Bank, Washington, DC, 2012)
This paper presents a study of willingness-to-pay of the Armenian Diaspora in the United States to protect Armenia's Lake Sevan, a unique and precious symbol of the Armenian cultural heritage. Dichotomous choice contingent valuation questions were asked by mail surveys to elicit respondents' willingness to pay for the protection of Lake Sevan. The results show that on average, each household of the Armenian Diaspora in the United States would be willing to provide a one-time donation of approximately US$80 to prevent a further degradation of Lake Sevan, and approximately US$280 to restore the quality of the lake by increasing its water level by 3 meters.